Reachability and stability of invariant set of a system of stochastic differential equations - Denisova , I. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
One investigates questions of attainability and stability of an invariant set of a linear system of stochastic differential equations for the corresponding nonlinear system. Conditions, under which stability in probability is possible, are singled out.